Towarzystwo Opieki nad Dziećmi „Gniazdo Łódzkie” w latach I wojny światowej - Sosnowska, Joanna (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2014)
„Gniazdo Łódzkie” Childcare Society had its genesis in 1907. Its origins are related to the charity campaign for children of workers from Łódź factories in connection with the revolution of 1905–1907. Members of the Childcare Society in Warsaw [Towarzystwo Opieki nad Dziećmi w Warszawie] became interested with the fate of orphans and half-orphans. During a meeting with Łódź aid providers (mainly physicians and clergymen) in February 1907 in Łódź, it was decided that a cooperation would be started and that the Łódź division of the Childcare Society would be opened with the name of „Gniazdo Łódzkie”. The first orphanage for children „with no home or care” was opened by the Society in July 1907 at Milscha 16 (at present, Kopernika street), in a leased tenement house. Over 30 children lived there; after a year, these numbers have increased up to 50. In 1914–1918, the number of residents was about 100. The Society took care of orphaned, homeless, and begging children (aged 4–10); with time, it also provided care to children of ill, crippled, or mentally disabled parents. Just before the outbreak of the World War I, the residents of „Gniazdo Łódzkie” Childcare Society moved to their own home build in Kały near Łódź, where an orphanage and a school were organized. The children lived in that new house for a few months only; in November 1914, the house was completely destroyed as a result of military action around Łódź. Then, residents of „Gniazdo Łódzkie” were moved to Łódź; they lived in „Dom Ludowy” of Christian Workers’ Association [Stowarzyszenie Robotników Chrześcijańskich] at Przejazd 34 (at present, Tuwima street). They ate in cheap soup kitchens. The Society tried to provide children from „Gniazdo Łódzkie” with optimum living conditions, also in the areas of care, education, health, and hygiene, during the war as well. Due to economic and organizational reasons, that was not an easy task. Among members of the Society, there were people who continued to provide care to orphans and homeless children even during the difficult years of German occupation.